Protective Effect of Vitamins C and E on Depot-Medroxyprogesterone Acetate-Induced Ovarian Oxidative Stress In Vivo - Atik Ismiyati; I. Wayan Arsana Wiyasa; Dwi Yuni Nur Hidayati (Journal of Toxicology)
A study was designed to investigate ameliorates effect of combined vitamins C and E able to against depot-medroxyprogesterone acetate- (DMPA-) induced ovarian oxidative stress in rat. Twenty-five female Wistar rats were divided into the following groups (n=5 rats each): control (untreated) (C); depot-medroxyprogesterone acetate (DMPA); DMPA plus green vitamin C (at dose of 0.2 mg/gram; 0.4 mg/gram; 0.8 mg/gram) and vitamin E (0.04 IU/gram). The treatment with combined vitamins C and E was performed for four weeks. Analysis of malondialdehyde (MDA) level as a marker of oxidative stress was done colorimetrically. Analysis of SOD level was done by enzyme linked immunosorbent assay (ELISA) technically. This increase in ovarium MDA was significantly (P<0.05) attenuated by medium dose treatments of combined vitamins C and E. DMPA insignificantly decreased SOD levels compared to the untreated group. This decrease in ovarian SOD level was significantly attenuated by all doses of the combined vitamins C and E. In conclusion, DMPA induces ovarian oxidative stress. Combined vitamins C and E prohibit the increase in ovarian lipid peroxidation, at least in part by modulating of superoxide dismutase. Therefore, this may provide an antioxidant therapy for attenuating the ovarian toxicity found in the DMPA therapy.